Eradicating potential of Achyranthes aspera - Vivek Dave; Swapnil Sharma; Km. Ruby; Sachdev Yadav; Jitendra Bajaj (International Journal of Phytomedicine, 2012)
The antioxidant activity of Achyranthes aspera methanolic aerial part extracts was investigated using the 2,2-diphenyl-1-picrylhydrazyl (DPPH) free radical-scavenging and ferric-reducing antioxidant power assays. Quantitative estimation of total flavonoid and phenolic content was performed followed by thin layer chromatography (TLC) to confirm the presence of secondary metabolites in the extract. From results of DPPH and ferric-reducing antioxidant power assays, it was found that methanolic aerial part extracts of Achyranthes aspera precipitates strong antioxidant (P < 0.005) activity compared to the ascorbic acid. The concentrations of total flavonoid and total phenolic content were found to be 47.6 mg RuE/g and 28.66 mg GAE/g respectively. The TLC study showed distinguished spots and revealed the presence secondary metabolites.